Who owns our work? - Salo, Dorothea (My University, 2010)
Much turmoil in the scholarly-communication ecosystem appears to revolve around simple ownership of intellectual property. Unpacking that notion, however, produces a fascinating tangle of stakeholders, desires, products and struggles. Some products of the research process, especially novel ones, are difficult to fit into legal concepts of ownership. As collaborative research burgeons, traditional ownership and authorship criteria are stretched to their limits and beyond, with many contributors still feeling short of due credit. The desire for access and impact brings institutions and grant funders into the formerly exclusive relationship between authors and publishers. Librarians, stripped of first-sale rights by electronic licensing, wonder about both access and long-term preservation. Emerging solutions to many of these difficulties threaten to cut publishers out of the picture altogether, perhaps a welcome change to those stakeholders who find publishers' behavior to block progress.
Keywords: copyright; scholarly communication